2022
DOI: 10.2224/sbp.10611
|View full text |Cite
|
Sign up to set email alerts
|

The association of perfectionism and active procrastination in college students

Abstract: It has been shown that perfectionism is a precursor to passive procrastination, which is a form of self-regulation failure, but little is known about the role of perfectionism in active procrastination. Thus, we sought to determine the relationship of high standards and discrepancy with active procrastination, which is a functional form of procrastination linked to better academic performance and psychological well-being. A convenience sample of 175 undergraduate students completed the Almost Perfect Scale-Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
2
0
3
Order By: Relevance
“…We found that students with ADHD symptoms scored higher on the passive procrastination scale, but lower on the active procrastination scale. A possible explanation can be that students who perceive discrepancies between their performance and performance goals are less likely to use active procrastination (Coutinho et al, 2022). It is noteworthy that active procrastination has been found to be a positive predictor of resilience (Ajaikumar, 2021), and it is also linked to self-efficacy and academic achievement (Hensley, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We found that students with ADHD symptoms scored higher on the passive procrastination scale, but lower on the active procrastination scale. A possible explanation can be that students who perceive discrepancies between their performance and performance goals are less likely to use active procrastination (Coutinho et al, 2022). It is noteworthy that active procrastination has been found to be a positive predictor of resilience (Ajaikumar, 2021), and it is also linked to self-efficacy and academic achievement (Hensley, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Namely, studies have relatively consistently shown that in threatening situations, maladaptive perfectionists most commonly use avoidance, or more precisely, procrastinations as a specific form of avoidance (Abdollahia et al, 2020;Dunn, Whelton & Sharpe, 2006;Kurtović et al, 2019;Smith et al, 2022). Procrastination is defined as unnecessary, conscious delaying of tasks in spite of the person's painful awareness of the negative consequences of this self-handicapping behavior (Coutinho, Menon, Ahmed & Fredricks-Lowman, 2022;Sederlund, Burns & Rogers, 2020). This irrational tendency towards postponing positively correlates with characteristics of maladaptive perfectionism such as hesitation and fear of mistakes, thus contributing to lower levels of academic achievement (Zhang, Bai & Yang, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Индиректни ефекти испитне анксиозности на успех на колоквијуму, остварени преко избегавања, у зависности од степена изражености дискрепанце Прокрастинација се дефинише као непотребно свесно одлагање завршавања задатака, упркос томе што је особа која упражњава овај вид самохендикепирајућег понашања болно свесна његових негативних последица(Coutinho, Menon, Ahmed & Fredricks-Lowman, 2022;Sederlund, Burns & Rogers, 2020). Ова ирационална склоност ка одлагању позитивно корелира са карактеристикама маладаптивног перфекционизма, попут оклевања и страха од грешака, те доприноси нижем академском постигнућу(Zhang, Bai & Yang, 2022).…”
unclassified
“…Por otra parte, la procrastinación estructurada puede beneficiar a una persona perfeccionista. Se ha demostrado que el perfeccionismo es un precursor de la procrastinación pasiva (Coutinho et al, 2022), por lo cual es conveniente acostumbrarse a dar por finalizada una tarea imperfecta. La tarea cumplirá su misión frente a los demás.…”
Section: Cómo Convivir Con Tu Procrastinaciónunclassified